How Educational Settings Inform Latino Student Identity and Achievement. (October 2019) - López, Francesca
Education research and policies focused on addressing achievement disparities among Latino youth often reflect discriminatory perspectives that assume deficiencies in Latino youth. To inform future efforts, this article briefly reviews research on academic and racial/ethnic identity formation for Latino youth and the role of educational settings in promoting Latino identity and achievement. Notably, educational contexts that incorporate asset-based pedagogy promote academic and racial/ethnic identities for Latino youth, which predict academic achievement. The research suggests developmentally appropriate ways teachers can engage with families and students to promote Latino youths' identity. Given that research often informs policy, the work reviewed here applies to both research and practice, with implications for professional research organizations, research standards, and policies that inform teacher preparation.